2016
DOI: 10.21082/bullittro.v25n1.2014.53-60
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH INTERVAL APLIKASI DAN WAKTU PENYEMPROTAN PESTISIDA NABATI SERAIWANGI TERHADAP HAMA Helopeltis antonii PADA TANAMAN KAKAO

Abstract: ABSTRAKPengaruh interval aplikasi dan waktu penyemprotan pestisida nabati seraiwangi (Cymbopogon nardus) terhadap hama pengisap buah Helopeltis antonii pada tanaman kakao, telah dilakukan di kebun PT. Inang Sari Kabupaten Agam Sumatera Barat. Percobaan disusun dalam Rancangan Acak Kelompok dengan delapan perlakuan dan empat ulangan, perlakuan tersebut adalah: In1Pg (interval aplikasi 1 x 1 minggu pagi hari), In1Sr (interval aplikasi 1 x 1 minggu sore hari), In2Pg (interval aplikasi 1 x 2 minggu pagi hari), In2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
0
7
0
7
Order By: Relevance
“…Attack of plant pests (OPT) handled by pra-attacks preventive before they occur or after attack extermination (curative) [5]. Environmentally friendly pest control was the use of biopesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Attack of plant pests (OPT) handled by pra-attacks preventive before they occur or after attack extermination (curative) [5]. Environmentally friendly pest control was the use of biopesticides.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions inferred that the late afternoon application had a more positive impact on lowering insect attacks. Nurmasyah (2014) also reported a similar phenomenon when treated cocoa plants with citronella extracts to control Helopeltis antonii. The lower attacks severity and percentage of attacks on late afternoon application were predicted to have a relation with the persistency of the active ingredient of the insecticides.…”
Section: Aphid Attack Severity and Percentage Of Attacked Plantsmentioning
confidence: 58%
“…Most insect species are poikilothermic creatures; thus, daily temperature affects the existence and position of the insect within the plants (Nowinszky & Puskás, 2013). A study conducted by Nurmasyah (2014) on applying citronellal extract to control Helopeltis antonii on cocoa revealed that the late-afternoon spraying gave different mortality on the insects than morning and mid-day applications. This research evaluated the efficacy of leaf extracts of T. sinensis and T. diversifolia and A. indica applied at different times to control aphids Macrosiphoniella sanborni Gillete in chrysanthemum considering the effects of botanical and time of application.…”
Section: Introductionmentioning
confidence: 99%
“…Pemanfaatan insektisida nabati seperti sereh wangi telah banyak diketahui dapat menurunkan tingkat serangan beberapa hama pada tanaman. Minyak sereh wangi dapat mengendalikan beberapa hama, diantaranya Helicoverpa armigera (Hasyim et al, 2010), lalat buah (Istianto, 2012), penggerek buah kakao (Wilis et al, 2013), hama penghisap buah lada, Dasynus piperis (Rohimatun dan Laba, 2013), hama penghisap buah kakao, Helopeltis antonii (Nurmansyah, 2014), penggerek buah mangga, Noorda albizonalis (Istianto dan Sumargono, 2015), dan. Plutella xylostella (Zahro et al, 2016).…”
Section: Abstrakunclassified